Postcolonial Ecocritical Perspectives in Indonesian Literature - Al - Qolbi, Labisal Fitri (Politeknik Siber Cerdika Internasional, 2025)
Colonialism in Indonesia has not only left political and cultural legacies, but also ecological damage recorded in literary works. This study aims to analyze the representation of human and environmental relationships in Indonesian literary works through a postcolonial ecocritical approach. Using a descriptive qualitative research method, data was collected from Indonesian novels, short stories, and poems with themes of colonialism and the environment. Thematic analysis showed the dominance of the themes of nature exploitation, local resistance, nature symbolism, and ecological decolonization. The results show that Indonesian literature is an important arena for building ecological awareness and critiquing colonial legacies. The findings have practical implications in the development of ecology-based literary studies and encourage the integration of sustainability perspectives in education and cultural policy.